Factors Affecting Patient Loyalty Through Intervening Patient Satisfaction at Bunda Hospital Purwokerto - I Putu Doddy; Ririn Wulandari (Sultan Publisher, 2022)
This paper aims to measure patients' satisfaction and comprehend their assumptions, which are important for hospital management in responding to customers' growing demand for quality healthcare services. This study used a quantitative approach in the form of a survey method. The findings revealed that Bunda Hospital Purwokerto's quality services have a positive effect on outpatient satisfaction. Successful service organizations understand the complexities and multidimensionality of quality. However, they must decide which aspects to compete in and improve, as well as strategically focus their efforts on responding to those customer-driven areas. Improvement in a hospital can be accomplished through a variety of methodologies, philosophies, and tools that focus on other areas of the business.